Self-efficacy beliefs as a predictor of quality of life and burnout among university lecturers - Matos, Mayara da Mota; Sharp, John G.; Iaochite, Roberto Tadeu (Frontiers in Education, 2022)
In this article we explore Brazilian lecturers’ self-efficacy beliefs as a predictor of quality of life and burnout drawing on the concept and theoretical framework of self-efficacy presented by Albert Bandura, the originator of Social Cognitive Theory. The questionnaires adopted for the research included the Brazilian Lecturer Self-Efficacy Scale (BLSES), the Maslach Burnout Inventory (MBI-ES) and the World Health Organization Quality of Life Assessment (WHOQOL-Bref). The participants were 1,709 lecturers from 78 universities in Brazil, most of whom had a doctoral degree. We analysed the data using descriptive and inferential statistics, performing structural equation modelling (SEM) and cluster analysis using IBM SPSS and Amos. We hypothesised that lecturer self-efficacy would be a positive predictor of quality of life and this, in turn, would be a negative predictor of burnout itself. SEM model fit indices fell within acceptable levels, with the overall model lending support to the stated hypothesis. In addition, lecturer self-efficacy was also a predictor of personal accomplishment in the MBI-ES. Regarding the cluster analysis, participants fell into five groups based on self-efficacy, quality of life and burnout questionnaire scores, each with associated personal, professional and academic characteristics. By way of discussion, we address reflections arising from findings to university life and working conditions, training needs and the need to establish career planning supported by studies that investigate the phenomenon of teaching in higher education in an integrated manner.